Importance of Gammarus in aquaculture - Harlioglu, Muzaffer Mustafa; Farhadi, Ardavan (Springer, 2018)
In recent years, there have been significant increases in the production and breeding of aquaculture species; for example, the gilt-head (sea) bream and seabass in salt water and trout, carp, and tilapia in fresh water., Amphipods in the genus Gammarus are used as a rich source of protein to feed various pet animals such as aquarium fish, lizards, and turtles, as well as in aquatic ecotoxicology and water quality assessment. Gammarus meal is used as a partial replacement (10-20%) of fish meal. However, the reproduction and rearing of Gammarus in intensive or semi-intensive conditions has not yet been carried out. Gammarus products (live, dried flakes, or powdered) transported to the markets are constituted from wild caught Gammarus. Due to the high price of these products, Gammarus aquaculture potentially has great economic benefits. Therefore, there is a need to focus on the importance of Gammarus in aquaculture. In the present review, the ecology and distribution of Gammarus, its importance in aquatic ecotoxicology and water quality assessment, the chemical analysis of Gammarus and factors affecting chemical composition of it, and the importance of Gammarus in fish nutrition are discussed. In addition, the economic importance and culture methods of Gammarus are also reviewed. This review will be beneficial for scientific investigators and fish-crustacean farmers.
Keywords: Gammarus; Aquaculture; Nutrition; Live food; Protein source; Fish meal